A DEVELOPMENTAL STUDY OF A SOLAR-ASSISTED MAIZE DRYER FOR QUALITY DRYING - F. Hussain; M. Ahmad; A. Ghafoor; Asif Tanvir (Journal of Animal and Plant Sciences, 2020)
This study was conducted for the design and development of solar assisted maize dryer to encounter the post-harvest losses. The development and experimental study was carried out in the Department of Farm Machinery and Power, University of Agriculture Faisalabad. The solar maize dryer consisted of a V-groove solar collector having 1.89 m2 collector area, drying chamber having diameter and height of 1.05m and 0.6m respectively. Three air ducts having diameter 0.15m have been provided within the drying chamber for drying homogeneity. In each of the experiments, 100 kg of maize with the initial moisture content of 24% (on average basis) was dried to 14% final moisture content. The average increase in temperature at the collector was 10 to 15 °C more than ambient temperature. Solar assisted maize dryer and open sun drying took 9 hours and 4 days respectively to dry maize up to desired moisture level. The maize samples were evaluated for quality analysis after drying. The percent (%) fats, carbohydrates, proteins and fiber ranged between 3.86-3.89%, 76.86-76.89%, 6.89-6.91% and 7.26-7.29% respectively. The breakeven analysis of the dryer showed that at 970 hours of working total revenue cost equals to the total cost of the dryer.
Keywords: Solar energy; collector; drying chamber; breakeven analysis